2020
DOI: 10.1002/anie.202005091
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Unprecedented Reactivity of a Mononuclear Nonheme Cobalt(III) Iodosylbenzene Complex

Abstract: A mononuclear nonheme cobalt(III) iodosylbenzene complex, [CoIII(TQA)(OIPh)(OH)]2+ (1), is synthesized and characterized structurally and spectroscopically. While 1 is a sluggish oxidant in oxidation reactions, it becomes a competent oxidant in oxygen atom transfer reactions, such as olefin epoxidation, in the presence of a small amount of proton. More interestingly, 1 shows a nucleophilic reactivity in aldehyde deformylation reaction, demonstrating that 1 has an amphoteric reactivity. Another interesting obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…Although data were recorded to 16 Å −1 , the data were analyzed only to 14.5 Å −1 owing to noise at high k. Data were subsequently processed and analyzed as previously reported using EXAFS123 and FEFF 9.4. 78 Errors to the models are reported as ε 2 values.…”
Section: Methodsmentioning
confidence: 99%
“…Although data were recorded to 16 Å −1 , the data were analyzed only to 14.5 Å −1 owing to noise at high k. Data were subsequently processed and analyzed as previously reported using EXAFS123 and FEFF 9.4. 78 Errors to the models are reported as ε 2 values.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Further, a recent study by Nam and coworkers reported the amphoteric reactivity of a cobalt(III) iodosylbenzene complex. 5 Nevertheless, various chemical properties and reaction mechanisms of metal iodosylarene species still remain unexplored.…”
mentioning
confidence: 99%
“…For decades, it has been actively debated whether a metal iodosylarene adduct, a precursor of the corresponding high-valent metal oxo species, acts directly as a reactive oxidant in the reactions involving a metal catalyst and an iodosylarene via a multiple-oxidant mechanism . To understand the nature of the metal iodosylarene species, several model complexes bearing an iodosylarene unit have been prepared and then characterized with various physicochemical methods including X-ray crystallography. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of importance here, is the fact that multiple‐oxidant mechanism, which consists of the involvement of multiple and distinct active metal‐oxygen species as well as metal‐oxidant adducts, has recently brought an unknown territory that needed to be explored, especially, new mechanistic pathways and reexamination of the nature of the actual active oxidants 17–21 …”
Section: Introductionmentioning
confidence: 99%